Low molecular weight epoxy resins syntheses - Król, P.; Król, B. (Polimery, 2022)
Low molecular weight epoxy resin synthesis in presence of NaOH as a classic catalyst for the addition reaction was compared with two new catalysts for epichlorohydrin (ECH) addition to dian, i.e. sodium metasilicate (MKS) and benzyltriethylammonium chloride (CBTA). Effect of molar ratio of ECH to the than on basic properties of EP was determined using GPC, IR, H-1-NMR and MS-ESI (Figs. 1-4), as well as content of epoxy groups (LE) and OH (L-OH) (Tables 1 and 2). Both new catalysts give higher reaction yields, but CBTA is more active. Resins received using CBTA have lower molecular weight (<400) and the associated therewith lower L-OH and higher LE values. Reaction of than ith ECH under applied synthesis conditions is complete. Both ddition reaction catalysts allow to reduce the ECH:dian ratio rom 6.5:1 in the NaOH process to 5:1, with improvement of inal product properties.